Sikap Hidup Masyarakat Jawa dalam Novel Orang-Orang Proyek Karya Ahmad Tohari dan Cerpen Karya Kuntowijoyo - Amalia, Riska Nur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to describe the attitude of the Javanese people in the novel project. The research method used is the sociology of literature. The results of the analysis indicated that the Javanese way of life in itself is the attitude of the Rila, nrima and patient, while the attitude of the society include itok-itok, wedi, isin, and shy. Suggested for further research to explore the meaning of the lines through a different approach, and readers can use the results of the study into the lives of the Javanese.